1983
DOI: 10.1093/ee/12.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Flight Patterns of European Corn Borer (Lepidoptera: Pyralidae) in New York1

Abstract: Seasonal flights of Ostrinia nubila/is (Hiibner) were monitored in 1981, using blacklight traps in 28 locations in central and western New York state. Calendar date of peak catch and heat unit accumulations indicated the presence of both univoltine and bivoltine biotypes, although before this study, only the latter was assumed to be present in these regions. Both biotypes were evident at 16 of the 28 trapping sites. Trap catches during the last S years of a IS-year study (1967)(1968)(1969)(1970)(1971)(1972)(19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…Recent investigations done on the well-studied Rhagoletis group have indicated that diapause diVerences associated with host races may have been the key trait that allowed for the initiation of diVerentiation, rather than simply initial diVerences in host aYliation (Feder et al 2003). Also, the European corn borer, Ostrinia nubilalis (Lepidoptera) in central New York state has a univoltine strain that emerges in July (between the two Xights of the bivoltine strain; Eckenrode et al 1983). As with our Papilio late Xight, there is a Z-linked factor that controls the postdiapause development time (Glover et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations done on the well-studied Rhagoletis group have indicated that diapause diVerences associated with host races may have been the key trait that allowed for the initiation of diVerentiation, rather than simply initial diVerences in host aYliation (Feder et al 2003). Also, the European corn borer, Ostrinia nubilalis (Lepidoptera) in central New York state has a univoltine strain that emerges in July (between the two Xights of the bivoltine strain; Eckenrode et al 1983). As with our Papilio late Xight, there is a Z-linked factor that controls the postdiapause development time (Glover et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these must be UZ x BE hybrids because they were generated at sites devoid of BZ borers. Initially, this seems improbable given the temporal differences in emergence of the bivoltine and univoltine insects, but blacklight (Eckenrode et al 1983) and pheromone trap surveys indicate that there is considerable overlap of the univoltine flight and the second flight of the bivoltine insects.…”
Section: Discussionmentioning
confidence: 99%
“…For a review of the early studies on life histories and the distribution of voltinism biotypes, see Brindley & Dicke (1963). Most recently, the voltinism patterns of Europ.ean corn borer in New York have been determined using blacklight traps (Eckenrode et al 1983) and direct field collection of larvae and pupae (Roelofs et al 1985). From these studies, it was clear that both bivoltine and univoltine populations exist in New York, often sympatrically.…”
mentioning
confidence: 99%
“…In New York state, populations are either bivoltine, with an early first generation and a late second generation, or univoltine, with a single generation in the middle of the season (22). Adults from the univoltine population are temporally isolated from those of the bivoltine population (23). Voltinism patterns reflect differences in postdiapause development (PDD) time, the time to pupation for over-wintering larvae under temperature and photoperiod conditions conducive to breaking diapause.…”
mentioning
confidence: 99%